The Incredible Years® Teacher Classroom Management programme and its impact on teachers' professional self‐efficacy, work‐related stress, and general well‐being: Results from the STARS randomized controlled trial. (13th April 2019) - Hayes, Rachel; Titheradge, Daniel; Allen, Kate; Allwood, Matt; Byford, Sarah; Edwards, Vanessa; Hansford, Lorraine; Longdon, Bryony; Norman, Shelley; Norwich, Brahm; Russell, Abigail Emma; Price, Anna; et al.
Abstract : Background: Teaching is a stressful occupation with poor retention. The Incredible Years® Teacher Classroom Management (TCM) programme is a training programme that research has demonstrated may be an effective intervention for improving children's mental health, but little research has explored any impacts there may be on the teachers' own professional confidence and mental health. Aims: In this paper, we evaluate whether TCM may lead to changes in teachers' well‐being, namely a reduction in burnout and an improvement in self‐efficacy and mental health. Sample: Eighty schools across the South West of England were recruited between September 2012 and September 2014. Headteachers were asked to nominate one class teacher to take part. Methods: Eighty teachers were randomized to either attend a TCM course (intervention) or not (control). TCM was delivered to groups of up to 12 teachers in six whole‐day workshops that were evenly spread between October and April. At baseline and 9‐month follow‐up, we measured teachers' mental health using the Everyday Feelings Questionnaire (EFQ), burnout using the Maslach Burnout Inventory‐General Survey (MBI‐GS), and self‐efficacy using the Teachers' Sense of Efficacy Scale‐Short (TSES‐Short). Results: Using linear regression models, there was little evidence of differences at follow‐up between the intervention and control teachers on the outcomes (the smallest p ‐value was .09). Conclusions: Our findings did not replicate previous research that TCM improved teachers' sense of efficacy. However, there were limitations with this study including low sample size.